Iron isotope behavior during fluid/rock interaction in K-feldspar alteration zone – A model for pyrite in gold deposits from the Jiaodong Peninsula, East China. (1st February 2018) - Zhu, Zhi-Yong; Jiang, Shao-Yong; Mathur, Ryan; Cook, Nigel J.; Yang, Tao; Wang, Meng; Ma, Liang; Ciobanu, Cristiana L.
Abstract: Mechanisms for Fe isotope fractionation in hydrothermal mineral deposits and in zones of associated K-feldspar alteration remain poorly constrained. We have analyzed a suite of bulk samples consisting of granite displaying K-feldspar alteration, Precambrian metamorphic rocks, and pyrite from gold deposits of the Jiaodong Peninsula, East China, by multi-collector inductively-coupled plasma mass spectrometry. Pyrites from disseminated (J-type) ores show a δ 56 Fe variation from +0.01 to +0.64‰, overlapping with the signature of the host granites (+0.08 to +0.39‰). In contrast, pyrites from quartz veins (L-type ores) show a wide range of Fe-isotopic composition from −0.78 to +0.79‰. Negative values are never seen in the J-type pyrites. The Fe isotope signature of the host granite with K-feldspar alteration is significantly heavier than that of the bulk silicate Earth. The Fe isotopic compositions of Precambrian metamorphic rocks across the district display a narrow range between −0.16‰ and +0.19‰, which is similar to most terrestrial rocks. Concentrations of major and trace elements in bulk samples were also determined, so as to evaluate any correlation between Fe isotope composition and degree of alteration. We note that during progressive K-feldspar alteration to rocks containing >70 wt% SiO2, >75 ppm Rb, and <1.2 wt% total Fe2 O3, the Fe isotope composition of the granite changes systematically. The Fe isotope signature becomes heavier as the degree of alteration increases. The extremely light Fe isotopic compositions in L-type gold deposits may be explained by Rayleigh fractionation during pyrite precipitation in an open fracture system. We note that the sulfur isotopic compositions of pyrite in the two types of ores are also different. Pyrite from J-type ores has a systematically 3.5‰-higher δ 34 S value (11.2‰) than those of pyrite from the L-type ores (7.7‰). There is, however, no correlation between Fe and S isotope signatures. The isotopic fractionation of sulfur is used to constrain a change in the f O2 of the hydrothermal fluids from which pyrite precipitated. This work demonstrates that the Fe isotope composition of pyrite displays a significant response to the process of pyrite precipitation in hydrothermal systems, and that systematic fractionation of iron isotopes occurs during fluid/rock reaction in the K-feldspar alteration zone of the Linglong granite. The implications of the results are that processes of mineralization and associated fluid-rock interaction, which are ubiquitously observed in porphyry-style Cu-Au-Mo and other hydrothermal deposits, may be readily traceable using Fe isotopes.